Membuat Animasi 2D menggunakan Java NetBeans : Animasi 2D - Asep Awaludin, Asep; Izra Rafif Rabbani, Izra; Perwira Syahida Rahman, Perwira; Sri Ghantika Maharani, Sri; Ines Heidiani Iksari, Ines (shofanah Media Berkah, 2024)
This study examines the creation of 2D animations using Java NetBeans. In this research, classes such as